Discourse on the Authority of the Judicial Commission in the Honorary Panel of the Constitutional Court in Indonesia - Kusnadi Umar; Sofyan Sofyan; Nur Azizah (LAW FACULTY UNISSULA, 2025)
The existence and position of the Judicial Commission has added to the list of independent state institutions (state auxiliary institutions) in the Indonesian state structure. The existence of the Judicial Commission in monitoring and enforcing the code of ethics for constitutional judges within the structure of the Honorary Council of the Constitutional Court has undergone a long discussion. For this reason, this research is normative research which aims to determine the legal position of the Judicial Commission in enforcing the judge's code of ethics and the ups and downs of the Judicial Commission's authority in the structure of the Honorary Council of the Constitutional Court. The results of the research show that the efficiency of the Judicial Commission's supervisory function actually strives for judges' compliance with the code of ethics and behavioral guidelines for judges in order to create public trust in judicial institutions in Indonesia, while the presence of the Judicial Commission in the supervision dimension of Constitutional Judges experiences a tug-of-war regarding the norms of Law Number 22 of 2004 concerning Judicial Commissions with material review in Decision 005/PUU-IV/2006, Law Law No. 8 of 2011 with a material review in the Constitutional Court decision no. 49/PUU-IX/2011, Law no. 4 of 2014 concerning Stipulation of Government Regulations in Lieu of Law no. 1 of 2013 concerning the Second Amendment to Law No. 24 of 2003 with material review in Decision No. 1-2/PUU-XII/2014 and Law No. 7 of 2020 with a material review in decision No, 56/PUU-XX/2022. Therefore, the institutional structure of the Judicial Commission in the Honorary Council of the Constitutional Court underwent several repositionings until it was finally judged as a form of legal contravention and unconstitutional (contrary to the 1945 Constitution).